2000
DOI: 10.1016/s0045-6535(99)00448-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity to and uptake of flumequine used in intensive aquaculture on the aquatic weed, Lythrum salicaria L.

Abstract: Phytotoxicity of Flumequine on the aquatic weed Lythrum salicaria L. was determined by two laboratory models: a single concentration test, by which the e ects of 100 mg l À1 were evaluated after 10, 20, 30 days and a multiple concentration test, by which the e ects of 5000±1000±500±100±50 lg l À1 were evaluated after 35-day exposure. 100 mg l À1 are highly toxic and signi®cantly decrease the growth of plants; this e ect increases with time. Concentrations between 5000 and 50 lg l À1 induced hormesis in plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 18 publications
3
31
1
Order By: Relevance
“…[14] The levels of contamination we found in such compartment (ng g −1 ) ( Table 2) seem not high enough to determine an appreciable contamination of seeds, as consequence of possible systemic absorption of drug, as already reported [13]. Nevertheless, the capability of different plants to absorb and store different antimicrobial drugs from different media [15][16][17][18][19][20] give risk concerns, and the possibility that some arable land could be more heavily contaminated as result of long-term fertilisation with pig slurries from intensive farming systems, should be not disregarded. To reduce possible environmental contamination of corn and/or other crop plants, the following management options could be suggested: reduction of the organic content matter of slurries, fraction to which antimicrobials binds, and dedicated lagoons for the storage of contaminated slurries, to be independently processed.…”
Section: Discussionmentioning
confidence: 59%
“…[14] The levels of contamination we found in such compartment (ng g −1 ) ( Table 2) seem not high enough to determine an appreciable contamination of seeds, as consequence of possible systemic absorption of drug, as already reported [13]. Nevertheless, the capability of different plants to absorb and store different antimicrobial drugs from different media [15][16][17][18][19][20] give risk concerns, and the possibility that some arable land could be more heavily contaminated as result of long-term fertilisation with pig slurries from intensive farming systems, should be not disregarded. To reduce possible environmental contamination of corn and/or other crop plants, the following management options could be suggested: reduction of the organic content matter of slurries, fraction to which antimicrobials binds, and dedicated lagoons for the storage of contaminated slurries, to be independently processed.…”
Section: Discussionmentioning
confidence: 59%
“…They may derive from different point or diffuse sources, such as animal husbandry, run-off from agricultural land treated with animal manure or slurry sludge, waste disposals or effluents from hospitals and households. Plant assays have shown that some PPCP are taken up by plants (Migliore et al 2000, Herklotz et al 2010, Winker et al 2010, Eggen et al 2011, Karnjanapiboonwong et al 2011, Shenker et al 2011. Uptake and transport within the plant differed for the different model plants and compounds.…”
Section: Microbial Loadsmentioning
confidence: 99%
“…They reported maximum tissue concentrations (ng/g) for OA (47), flumequine (-600), OTC (1200), and florfenicol (513). Migliore et al (2000) exposed an aquatic weed (Lythrum salicaria L.) to flumequine. After 35 days, the dry-weight tissue concentrations were in the ppm range: 13.3, 8.7, 0.7, 0.3, and 0.2 Ilg/g at flumequine aqueous concentrations of 5000, 1000,500, 100, and 50 Ilg/L, respectively.…”
Section: Uptake By Aquatic Plants and Aerial Invertebratesmentioning
confidence: 99%